Effect of Intraocular Pressure on Aerosol Density Generated by Noncontact Tonometer Measurement. Issue 11 (November 2020) - Tang, Yuan; Li, Chunchun; Chen, Yanyan; Chen, Zhangyan; Zhang, Peihua; Wang, Aisun; Huang, Xiaoqiong; Qu, Jia; Li, Mengchen; Ma, Siwen; Vasudevan, Balamurali
Abstract : Precis: Aerosols generated by a noncontact tonometer (NCT) were quantified. There was a positive correlation between aerosols and intraocular pressure (IOP), and the concentration of aerosols beside the air jet port was the highest. Purpose: To investigate the effects of IOP on the aerosol density generated during the use of an NCT and provide references and suggestions for daily protection of ophthalmic medical staff during the coronavirus disease-19 (COVID-19) outbreak. Objective and Methods: This cross-sectional clinical trial included 214 eyes of 140 patients from a hospital in Wenzhou city, Zhejiang Province. All subjects' IOPs were measured by an NCT (39 eyes with low IOP, 90 eyes with normal IOP, 37 eyes with moderately high IOP, and 48 eyes with very high IOP) between March 7 and June 17, 2020. The density of particulate matter (PM) 2.5 and PM10 generated during the process of IOP measurement with an NCT was analyzed. IOP values were recorded simultaneously. The aerosols generated during different IOP measurements were plotted in scatter plots. Results: PM2.5 was generated more at the air jet port of the tonometer during the process of IOP measurement ( H =2.731, P =0.019). Larger quantities of PM2.5 and PM10 were generated when the IOP was higher, and these differences were statistically significant (PM2.5: H =119.476, P <0.001; PM10: H =160.801, P <0.001). Linear correlation analysis with one variable demonstrated that IOP had significantly positive correlations with PM2.5 ( r =0.756, P <0.001) and PM10 ( r =0.864, P <0.001). Conclusions: Aerosols can be generated while using an NCT to measure IOP, and aerosols and IOP are positively correlated. Patients with moderately high IOP or very high IOP tend to generate more aerosols during the IOP measurement. The concentration of aerosols beside the air jet port was the highest.